2016
DOI: 10.1111/ijau.12074
|View full text |Cite
|
Sign up to set email alerts
|

Do Mother and Father Auditors Have Equal Prospects for Career Advancement?

Abstract: This research investigates whether parental role and gender are associated with career advancement for professional female and male auditors employed by international audit firms in Denmark. Management at four levels, from partner to lower level non-management employee, are examined to determine whether a relationship holds between being a parent and gender. We find that more parents achieve advancement to higher levels of employment than non-parents. However, mothers are significantly disadvantaged relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
(59 reference statements)
1
10
0
2
Order By: Relevance
“…Nemoto (2013) cautions that the antidiscrimination policies may not always prevent gender bias as corroborated by the 'invisible' barriers that women encounter in their career trajectories. As observed in this study, and in support of the existing literature, when organisations create female disadvantage and male advantage, women's prospects for career advancement are curtailed (Acker, 1990(Acker, , 2012Kristensen et al, 2017;Martin, 2001). Despite the vast potential to contribute positively to the goals of the organisation, women like Participant 3 find it difficult to 'crack' the glass ceiling (Davis & Maldonado, 2015).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Nemoto (2013) cautions that the antidiscrimination policies may not always prevent gender bias as corroborated by the 'invisible' barriers that women encounter in their career trajectories. As observed in this study, and in support of the existing literature, when organisations create female disadvantage and male advantage, women's prospects for career advancement are curtailed (Acker, 1990(Acker, , 2012Kristensen et al, 2017;Martin, 2001). Despite the vast potential to contribute positively to the goals of the organisation, women like Participant 3 find it difficult to 'crack' the glass ceiling (Davis & Maldonado, 2015).…”
Section: Discussionsupporting
confidence: 75%
“…The women's experiences revealed that the hours of work were more suitable for male life patterns. However, previous researchers have unveiled how hours of work are socially constructed along gendered life cycles (Kristensen et al, 2017). Hours of work are constructed around the ideal worker who is essentially a man because he is unencumbered by home and family responsibilities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations